Calculation of Laser-Induced Breakdown Spectroscopy Plasma Temperature using Boltzmann Equation using two Netral Cu line Emission - Milano, Vincent; Hery, Suyanto; Yoga, Ida Bagus Ketut (BULETIN FISIKA; Vol 25 No 1 (2024): BULETIN FISIKA February Edition, 2024)
Research have been conducted about calculating the plasma temperature using Laser-Induced Breakdown Spectroscopy (LIBS), located in Udayana University’s Laboratorium Penelitian Terpadu FMIPA. The calculation of Plasma Temperature is done using the Boltzmann Equation using the emission intensity and area under the curve of two wavelength from Cu neutral atom Cu I 521.82 nm and Cu I 510.55 nm. The intensity of Neutral Cu atom is obtained from focusing the Nd:YAG laser (1064 nm, 7 ns) with 80 mJ energy to the surface of Bras 6s (or 99.99%) slab in the air with 1 atm pressure and Helium gas with 60 mL/s flowrate, which will generate a plasma. The Photon emission from Cu neutral atoms in plasma will be caught by spectrometer HR 2500+ (14.336 CCD pixel, 200-800 nm). The average plasma temperature by delay time detection using intensity and area ratio is (8976.40±160.34) K and (13119.20±435.23) K respectively. In Helium gas, the temperature is (12261.21±419.06) K using intensity ratio and (16882.41±678.18) K using Area ratio.